Genome trees constructed using five different approaches suggest new major bacterial clades - Wolf, Yuri I (BioMed Central, 2001)
BACKGROUND: The availability of multiple complete genome sequences from diverse taxa prompts the development of new phylogenetic approaches, which attempt to incorporate information derived from comparative analysis of complete gene sets or large subsets thereof. Such attempts are particularly relevant because of the major role of horizontal gene transfer and lineage-specific gene loss, at least in the evolution of prokaryotes. RESULTS: Five largely independent approaches were employed to construct trees for completely sequenced bacterial and archaeal genomes: i) presence-absence of genomes in clusters of orthologous genes; ii) conservation of local gene order (gene pairs) among prokaryotic genomes; iii) parameters of identity distribution for probable orthologs; iv) analysis of concatenated alignments of ribosomal proteins; v) comparison of trees constructed for multiple protein families. All constructed trees support the separation of the two primary prokaryotic domains, bacteria and archaea, as well as some terminal bifurcations within the bacterial and archaeal domains. Beyond these obvious groupings, the trees made with different methods appeared to differ substantially in terms of the relative contributions of phylogenetic relationships and similarities in gene repertoires caused by similar life styles and horizontal gene transfer to the tree topology. The trees based on presence-absence of genomes in orthologous clusters and the trees based on conserved gene pairs appear to be strongly affected by gene loss and horizontal gene transfer. The trees based on identity distributions for orthologs and particularly the tree made of concatenated ribosomal protein sequences seemed to carry a stronger phylogenetic signal. The latter tree supported three potential high-level bacterial clades,: i) Chlamydia-Spirochetes, ii) Thermotogales-Aquificales (bacterial hyperthermophiles), and ii) Actinomycetes-Deinococcales-Cyanobacteria. The latter group also appeared to join the low-GC Gram-positive bacteria at a deeper tree node. These new groupings of bacteria were supported by the analysis of alternative topologies in the concatenated ribosomal protein tree using the Kishino-Hasegawa test and by a census of the topologies of 132 individual groups of orthologous proteins. Additionally, the results of this analysis put into question the sister-group relationship between the two major archaeal groups, Euryarchaeota and Crenarchaeota, and suggest instead that Euryarchaeota might be a paraphyletic group with respect to Crenarchaeota. CONCLUSIONS: We conclude that, the extensive horizontal gene flow and lineage-specific gene loss notwithstanding, extension of phylogenetic analysis to the genome scale has the potential of uncovering deep evolutionary relationships between prokaryotic lineages.